Middle management perceptions of the Six Sigma methodology - Tziatas, Ioannis Anastasios (My University, 2011)
In today's competitive market, organisations strive to maximise profits. Many tools are used in an attempt to achieve this, one of which is Six Sigma. The purpose of this research has been to investigate the perceived view of middle managers on Six Sigma. An extensive literature survey was carried out on the subject. Qualitative research was conducted to investigate how South African managers view Six Sigma. The results suggest that for the participating organisations, the perceptions of local managers do not differ from views expressed in overses literature. The main findings of the research were that managers define or view Six Sigma in many different ways. In addition they do see value in applying Six Sigma in a wide range of applications, and that for it to succeed, support is required from both senior management and the people implementing it. The findings can be a useful summary for managers executing Six Sigma initiatives.
MBA - WBS
Keywords: Six Sigma methodology